2015
DOI: 10.1016/j.ijpe.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint and responsiveness trade-offs in supply chain network design

Abstract: a b s t r a c tConcern related to sustainability and greenhouse gases has grown among citizens as well as firms, which are increasingly committing to carbon emission reduction targets. However, firms' emissions come from direct and indirect sources, and from the different stages of their supply chain. Therefore, comprehensive supply chain approaches are essential to ensure the cost-effectiveness of carbon management strategies. These approaches should capture operational and environmental trade-offs arising fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 30 publications
0
64
0
2
Order By: Relevance
“…The environmental impact of freight transportation is increasingly considered in decision-making related to transport (Bouchery and Fransoo, 2015, Mostert et al, 2017a, Mostert et al, 2017b or supply chain network design (Wang et al, 2011, Chaabane et al, 2012, Martí et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental impact of freight transportation is increasingly considered in decision-making related to transport (Bouchery and Fransoo, 2015, Mostert et al, 2017a, Mostert et al, 2017b or supply chain network design (Wang et al, 2011, Chaabane et al, 2012, Martí et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the percentage reduction of profit and carbon emission of a high-efficiency firm were lesser than that of low-efficiency firm. Martí et al [31] proposed a supply chain network model with demand uncertainty which includes supply chain responsiveness decisions under different carbon policies. They also showed the effect of different carbon policies on supply chain costs and network design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These models include linear programming (LP), nonlinear programming (NLP), mixed integer programming (MIP), mixed integer linear programming (MILP), goal programming (GP), robust programming (RP), stochastic programming (SP), dynamic programming (DP), possibilistic programming, queuing theory, fuzzy mathematical programming, and bi-objective programming [58,[69][70][71][72][73][74][75].…”
Section: Quantitative Modelsmentioning
confidence: 99%